MENINGKATKAN KEMAMPUAN REPRESENTASI MATEMATIS MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) MAHASISWA TADRIS MATEMATIKA - Mutazam (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Based on the early observation and test results of mathematical representation ability , it is shown that the ability of mathematical representation of the students was still low so that it needed to be improved. In this case, Problem Based Learning (PBL) model could be one of the alternatives in implementing mathematics learning in the class. PBL model consists of five phases which are students’ orientation on the problem, organizing the students to study, guiding students’ experiences, developing and presenting attainments, and also, analyzing and evaluating problem solving process. Each phase could improve students’ mathematical representation ability in the learning. PBL model implementation in the learning. This research is a classroom action research that implemented in three cycles. Students were given a quiz as the final test in every cycle to measure their mathematical representation ability. The result shows that mathematics learning using the PBL model could improve students’ mathematical representation ability. It is shown by the improvement of average score of mathematical representation ability and the presentation of quantity of students who reach Minimum Learning Mastery Standard in each cycle.